(untitled) (Journal of the College of Basic Education, 2022)
The aesthetic heritage is part of the artistic and intellectual references of the Muslim artist, as he wanted through this trend to build an artistic achievement based on commitment and idealism, as Islamic art is an art that believes in monotheism and testifies to divinity. Values ​​turned into flat forms and devoid of any significance in the visible world, to return to a Sufi tendency that renounces everything that is emotional, sensual, or accidental. Antiquity